Фаворит: роман-хроника времен Екатерины II в 2 т. (В. С. Пикуль) - Пикуль Валентин Саввич (1991)
Экземпляры: абонемент (20190513) / Инвентарный номер: 18299 / Цена: 12.10 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 32 / ББК: 84(2Рос=Рус)6